Enhancing the photocatalytic properties of nickel oxide nanoparticles via iron doping: Efficient degradation of eosin yellow dye - Burhan Uddin; Md. Omor Farque; Md. Moniruzzaman; Md. Jasim Uddin; Md. Kamrul Hossain; Sayeda Halima Begum (Chemical Physics Impact)
In this study, iron (Fe) doping was employed to enhance the photocatalytic performance of Nickel Oxide Nanoparticles (NiONPs), particularly in the degradation of Eosin Yellow, a representative organic dye. NiONPs were synthesized via a chemical precipitation method using nickel nitrate hexahydrate as the precursor, with iron (III) nitrate nonahydrate introduced as the dopant to achieve Fe concentrations of 2 %, 4 %, 6 %, and 8 % in the NiONPs. The resulting Fe-doped NiONPs were characterized using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). The photocatalytic performance was evaluated by monitoring the degradation of Eosin Yellow under visible light irradiation. The characterization studies confirmed successful Fe doping in the NiO lattice, resulting in structural and compositional changes. Photocatalytic testing revealed that Fe doping enhanced the degradation efficiency of NiONPs for Eosin Yellow. Among the tested samples, 4 % Fe-doped NiONPs showed an impressive increase of nearly 30 % in degradation efficiency compared to undoped NiONPs. This enhancement is attributed to improved charge separation and increased light absorption, driven by the Fe dopant's influence on the electronic structure of NiONPs. The improved photocatalytic performance of Fe-doped NiONPs can be explained by the reduction of electron-hole recombination, which enhances the generation of reactive species responsible for dye degradation. These findings highlight the potential of Fe-doped NiONPs for applications in environmental remediation, especially in wastewater treatment processes aimed at removing organic pollutants.